Farmers as Researchers: In‐depth Interviews to Discern Participant Motivation and Impact. (1st November 2019) - Thompson, Laura J.; Glewen, Keith L.; Elmore, Roger W.; Rees, Jennifer; Pokal, Sayli; Hitt, Brianna D.
Abstract : On‐farm research is a method for transferring technology to farmers, validating small plot research, generating new discovery, and evaluating field‐scale, site‐specific management techniques. Little has been done to understand what motivates farmers to participate in on‐farm research and what the impact of their participation is on their decision making and farm profitability. This study evaluated the University of Nebraska‐Lincoln's over 25 yr‐old on‐farm research program using a semi‐structured, in‐depth interview tool to complete interviews with a stratified sample of 40 of the 140 past‐participants. The focus of this qualitative study was obtaining rich descriptions of farmer participants to better understand motivation for involvement in an on‐farm research program, participant research experiences, and the economic impacts of an on‐farm research program. Quantitative statistical analyses of the qualitative data are included for informational purposes; however, our conclusions focus on the qualitative analysis. Farmers participated in an on‐farm research program for a variety of reasons, most commonly for economic gain. Positive experiences were largely credited to the interactions with university faculty and other farmers. The participating farmers' perception regarding whether or not the project took too much time was unrelated to whether weigh wagons or yield monitors were used. Farmers were interested in many aspects of research, including project ideation, experimental design, and statistical analysis. Participating farmers' satisfaction in their experience and implementation of research results was not dependent on the farmers independently generating their research topic. The most impassioned suggestion from the farmer research participants was to develop innovative research projects. Core Ideas In‐depth interviews with participants in an on‐farm research program generated insights into motivation for participation and program impact. Farmers participated in the program for a variety of reasons including economic gain, seeking answers to a specific questions, general curiosity, and a desire for reliable and unbiased research results. Positive experiences in the on‐farm research program were largely credited to interactions with university faculty and other farmers. The origin of the research topic or idea did not influence participant satisfaction in their experience or implementation of the results. Seventy‐five percent of interviewees had put their research results into practice in their farm operation, either by making a change based on results or by not making a change as the research confirmed their current practice.